Growth Analysis of Production of Food Crops and Population Growth for Food Security in Pakistan: Growth Analysis of Production of Food Crops and Population - Muhammad Islam; Farrukh Shehzad; Abdul Qayyum; Mirza Waseem Abbas; Rabia Siddiqui (Proceedings of the Pakistan Academy of Sciences: B. Life and Environmental Sciences, 2023)
Food availability is one of the important pillars of food security. It is essential to ensure food availability in the world to avoid starvation. The key concern of the present study is to integrate the fluctuations in the growth rate of the population and important food crop production using time series data from 1950-2021. Semi-log compound growth rate models are applied for the projection, Cuddy-Della and Valle instability index are used for the stability analysis, and decomposition analysis models are applied to determine the contribution of factors toward production. Semi log compound growth rate model indicates that the population of Pakistan is increasing rapidly, while the contribution of productivity and area of all food crops are not enough to meet food sustainability. The growth rate in the area and production of Wheat, Rice, and Maize are positive, while it is negative for Sorghum (jawar), Millet (bajra), and Barley. For areas, a low degree of instability is prevailing for Wheat, Rice, Maize, Sorghum (jawar), and population, while the medium is for Millet (bajra) and Barley. For yield, the degree of instability is low for all food crops except Maize, which lies in the medium instability index. Semi log compound growth rate model was found best fitted for area and productivity for all food crops, while for the production side, it is found best for Wheat, Rice, and Maize and bit fit for Sorghum (jawar), Millet (bajra) and Barley. Decomposition analysis model predicted that crop productivity is a major concern to attain food security in Pakistan.